Retreatment with anti-EGFR monoclonal antibodies in metastatic colorectal cancer: Systematic review of different strategies. (February 2019) - Mauri, Gianluca; Pizzutilo, Elio Gregory; Amatu, Alessio; Bencardino, Katia; Palmeri, Laura; Bonazzina, Erica Francesca; Tosi, Federica; Carlo Stella, Giulia; Burrafato, Giovanni; Scaglione, Francesco; Marsoni, Silvia; Siravegna, Giulia; et al.
Highlights: Anti-EGFR retreatment has been studied in patients with metastatic colorectal cancer. The underlying biological rationale has been recently elucidated. It is categorized in: rechallenge, reintroduction, sequence or dose-intensification. In molecularly selected patients, rechallenge provides best results. Abstract: Background: Despite advances in precision oncology and immunotherapy of tumors, little progress has been made in metastatic colorectal cancer (mCRC) in recent years. Therefore, making the most of available therapies is a necessity. Several studies, based on the pulsatile behavior of RAS clones under EGFR blockade, investigated whether readministration of EGFR-targeted agents is effective beyond second line. Methods: A systematic review of studies of retreatment with anti-EGFR monoclonal antibodies has been performed from January 2005 to December 2018 according to PRISMA criteria from PubMed, ESMO and ASCO meetings libraries and Clinicaltrial.gov. Efficacy has been evaluated as objective response rate and survival in available publications. In addition, type and incidence of side effects occurring during on anti-EGFR retreatment have been considered. Results: 26 publications have been retrieved, of which 20 full-text articles and 6 abstracts and categorized as for the retreatment strategy into five groups: rechallenge (n = 10), reintroduction (n = 4), sequence (n = 5), dose escalation (n = 1) and mixed (n = 6). Data of efficacy displayed high heterogeneity across different strategies (objective response rate, ORR = 0.0–53.8%; disease control rate, DCR = 24.0–89.7%), with best results in the setting of rechallenge (ORR = 2.9–53.8%; DCR = 40.0–89.7%). Conclusions: Rechallenge with anti-EGFR provides clinical benefit in molecularly selected mCRC patients beyond second line. Further ctDNA-guided studies comparing this option of treatment with current approved advanced line treatments are warranted.